Obravnava bolečine v trebuhu pri zdravniku družinske medicine - Kopčavar Guček, Nena (Medicinski razgledi, 2010)
Abdominal pain is a common presentation in outpatient settings and is challenging to diagnose. As the physician of the first contact, the family physician should be able to recognize life-threatening conditions. This article describes the diagnostic procedures for elucidating abdominal pain in family practice. Since history of the actual disease and clinical examination of the patient are the most important tools, special attention is devoted to them. Radiating pain has been observed as a diagnostic challenge, but laboratory tests and imaging techniques do improve the chances of defining thecause of the disease. Women and the elderly should warrant special attention when evaluating abdominal pain. Since the assessment of abdominal pain is of key importance in the outpatient setting, family physicians play animportant role in recognizing this life-threatening condition.
Keywords: diagnostika; družinska medicina; bolečina; trebuh